Fra Celti Cenomani e Romani: La ceramica nel territorio veronese dal III sec. a.C. all’età augustea: novità e persistenze - Biondani, Federico (Rei Cretariae Romanae Fautorum Acta, 2022)
In this paper we analyze the changes that occur in the ceramic documentation (especially regarding funeral testimonials) in the plain of Verona from the 3rd century BC (when it was part of the territory of the Celts Cenomani) and the Augustan Age (when the process of political Romanization was already over). – 3rd–early 2nd century BC (LT B–C1): in this period the Verona plain was populated, at least in part, by Celtic groups. The scarce documentation shows ceramics probably connected with the Celtic area, the Veneto area (grey pottery) and importations from Volterra (black-glazed ware); – 175–125/120 BC (LT C2): the Celtic population was consolidated, but at the same time the presence of Rome strengthened (e.g., in 148 BC Via Postumia was constructed right in the territory of the Cenomani): pottery was Celtic but also connected with the Veneto and the Rhaetian area. Also «Roman» types (black glaze pottery and imitations) have been discovered; – 125/120–70/60 BC (LT D1): in this period Transpadani had ius Latii (89 BC) and oppidum of Verona was built on the left bank of the river Adige. The plain of Verona shows a ceramic facies still Celtic, but also pottery connected with Veneto and the Rhaetian area has been found, while the «Roman» ceramics (black-glaze ware and imitations; thin walled pottery) was spreading; – 70/60–30 BC (LT D2): in this period Transpadani had Roman citizenship (49 BC). The new town of Verona was founded on the right bank of the Adige; «Roman» ceramics was more and more used (black glaze pottery and imitations; thin walled pottery; some types of common fine ware); coarse ware remained substantially local; – the Augustan Age: in this period, which marks a widespread population in the territory as a result of centuriatio, ceramic facies was fully Roman; some persistence of the local tradition can be found in the coarse ware.